Efektifitas Self-Guided Progressive Muscle Relaxation (PMR) Berbasis Teknik Jacobson dengan Kombinasi Instrumental untuk Mahasiswa Keperawatan yang Mengalami Kelelahan Psikologis (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
Psychological fatigue is a common condition experienced by nursing students due to heavy academic workload, clinical practice demands, and emotional pressure during the learning process. This condition may negatively affect concentration, learning motivation, and overall mental health. One non-pharmacological intervention strategy proven effective in reducing stress and psychological fatigue is Progressive Muscle Relaxation (PMR) based on Jacobson’s technique. In this community service program, PMR was combined with instrumental music to provide a more optimal relaxation effect and to be easily applied by students independently. The purpose of this activity was to provide education, training, and hands-on experience for students in practicing Self-Guided PMR combined with instrumental music as a preventive and promotive effort for mental health. The program was carried out on Thursday, August 14, 2025, involving 15 nursing students as participants. The stages of implementation included delivering material on PMR concepts and mental health, demonstrating Jacobson’s technique, independent practice of PMR with instrumental music, and a reflection session to explore participants’ experiences. The evaluation results indicated that most students reported feeling calmer, more relaxed, experiencing reduced muscle tension, and decreased symptoms of psychological fatigue after the intervention. In addition, students stated that this technique was easy to practice independently, making it a potential simple strategy to maintain mental health throughout their nursing studies. In conclusion, the implementation of Self-Guided PMR based on Jacobson’s technique combined with instrumental music was effective in reducing psychological fatigue among nursing students and in increasing awareness of the importance of independent relaxation practice as part of maintaining mental and physical balance.